Differences in physical habitat simulation system modelling results using benthic or pelagic fish species as indicators in Peruvian Andes–Amazon rivers. (15th February 2020) - Oyague, Eduardo; Vera, Adrián; Cabrejos, Lucía; Franco, Pablo
Abstract: Aquatic organisms with different adaptations are used as indicators in physical habitat simulation system models. Those adaptations are critical for determining the shape of the weighted usable area/width curve and for recommending values of environmental flows. The main objective of this study is to compare the use of benthic native species ( Astroblepus taczanowskii and Astroblepus vanceae ) versus the introduced Oncorhynchus mykiss (rainbow trout) as target indicators for PHABSIM modelling in the Andean–Amazon piedmont rivers. We used adjusted probability distribution functions with L‐moments analyses for developing curves of use and preference to evaluate the efficiency of each indicator. Two hydraulic modelling sections were established in the Ulcumayo River with 21 and 27 cross sections, respectively. Native benthic species are usually dominant but scarcely used as focus organisms for environmental flows modelling. These species are associated with fast running and shallow waters, which makes them potentially more sensitive to the effects of flow reduction. Our results indicated that the native species were more restricted to velocity and depth than O. mykiss . Using selection curves in PHABSIM modelling, it is required between 10% to 94% of the mean monthly flow to preserve 90% of the available habitat for Astroblepus during the dry season (May to November). In contrast, rainbow trout requires 5% to 88% of the mean monthly flow. We conclude that a multispecies approach is useful for determining the required environmental instream flows contributing to a better sustainable condition for the Neotropical mountain rivers.